2004
DOI: 10.1159/000081246
|View full text |Cite
|
Sign up to set email alerts
|

Free IGF-I, IGFBP-1, and the Binary Complex of IGFBP-1 and IGF-I Are Increased during Human Pregnancy

Abstract: Background/Aims: To investigate changes in free insulin-like growth factor I (IGF-I) and IGF-binding protein 1 (IGFBP-1) complexed IGF-I during human pregnancy. Methods: Overnight fasting serum was obtained in a longitudinal design from 11 women with non-complicated pregnancy at gestation weeks 6–10, 16–20, 24–28 and 35–38 and, for comparison, 5 weeks post-partum. All samples were analyzed for total and free IGF-I and IGF-II, IGFBP-3 and IGFBP-3 proteolysis, total and non-phosphorylated (np-) IGFBP-1, and IGFB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 46 publications
2
3
0
Order By: Relevance
“…We showed that serum hsCRP and MMP-8 decreased while IGFBP-1 and phIGFBP-1 increased during pregnancy, regardless of the intervention or GDM status. Our findings with respect to the changes of IGFBP-1 and hsCRP during pregnancy are in agreement with the results of previous studies [60][61][62][63] but some discrepancies exist regarding hsCRP, e.g., a study conducted in non-obese pregnant women with GDM detected an elevation in hsCRP along with the gestational age [64]. The MMP-8 level declined, which is in contrast to previous studies in which increased MMP-8 levels were related to adverse pregnancy outcomes including preterm delivery [65] or high amniotic fluid MMP-8 in intra-amniotic inflammation [5].…”
Section: Discussionsupporting
confidence: 93%
“…We showed that serum hsCRP and MMP-8 decreased while IGFBP-1 and phIGFBP-1 increased during pregnancy, regardless of the intervention or GDM status. Our findings with respect to the changes of IGFBP-1 and hsCRP during pregnancy are in agreement with the results of previous studies [60][61][62][63] but some discrepancies exist regarding hsCRP, e.g., a study conducted in non-obese pregnant women with GDM detected an elevation in hsCRP along with the gestational age [64]. The MMP-8 level declined, which is in contrast to previous studies in which increased MMP-8 levels were related to adverse pregnancy outcomes including preterm delivery [65] or high amniotic fluid MMP-8 in intra-amniotic inflammation [5].…”
Section: Discussionsupporting
confidence: 93%
“…However, as discussed previously [21], their nutritional status is probably typical of that of Swedish women and not very different from women in other developed countries. Regarding the variability of the maternal IGF system components before, during and after pregnancy, our observations were similar to those reported for other study populations [4, 10, 13]. The changes we observed during pregnancy are also in agreement with results obtained in other Western populations for IGF-I [4, 10, 13], IGF-II [4, 10, 13], IGFBP-1 [4, 10], IGFBP-3 [10, 11, 13] and protease activity against IGFBP-3 [13,14,15].…”
Section: Discussionsupporting
confidence: 91%
“…However, high concentrations of IGFBP-1 in maternal serum will decrease circulating ‘free’ IGF-I inhibiting this anabolic effect, thus counteracting fetal growth. Such a mechanism can be reconciled with observations showing that serum concentrations of ‘free’ IGF-I are markedly increased during late pregnancy [13]. …”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations